2012
DOI: 10.1007/s00203-012-0834-x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of DNA repair and membrane integrity in heat resistance of Deinococcus radiodurans

Abstract: To study the effects of heat shock on Deinococcus radiodurans and the role of DNA repair in high temperature resistance, different strains of D. radiodurans (wild type, recA, irrE, and pprA) were treated with temperatures ranging from 40 to 100 °C under wet and dry conditions. The mutant strains were more sensitive to wet heat of ≥60 °C and dry heat of ≥80 °C than the wild type. Both wild-type and DNA repair-deficient strains were much more resistant to high temperatures when exposed in the dried state as oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…D. radiodurans irradiated with 4 kGy loses up to 30% wet weight resulting from the loss of polysaccharides into the growth medium, which suggests permeability alterations in the cell envelope ( Mitchel, 1976 ). For retaining membrane integrity, D. radiodurans cells were much more resistant to high temperatures when exposed in the dried state as opposed to cells in suspension ( Bauermeister et al , 2012 ). The R1Δ dr1790 mutant showed a high proportion of damaged membranes (20% red cells observed in the mutant field) compared with wild type and complemented mutant strains.…”
Section: Discussionmentioning
confidence: 99%
“…D. radiodurans irradiated with 4 kGy loses up to 30% wet weight resulting from the loss of polysaccharides into the growth medium, which suggests permeability alterations in the cell envelope ( Mitchel, 1976 ). For retaining membrane integrity, D. radiodurans cells were much more resistant to high temperatures when exposed in the dried state as opposed to cells in suspension ( Bauermeister et al , 2012 ). The R1Δ dr1790 mutant showed a high proportion of damaged membranes (20% red cells observed in the mutant field) compared with wild type and complemented mutant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Previous desiccation, on the other hand, can also be beneficial to vacuum tolerance as demonstrated in storage experiments of the closely related D. radiodurans compared with storage at ambient air (Bauermeister et al, 2012). Endurance of vacuum exposure has also been demonstrated for D. radiodurans, D. aerius, and D. aetherius for 1 year with a 10-to 100-fold reduction in culturability (Kawaguchi et al, 2013).…”
Section: Enzymatic Activity Of Biofilms and Planktonic Cells Of D Gementioning
confidence: 92%
“…Knockout of the dsr11 affects the expression of genes involved in cell membranes. Previous reports have shown that heat stress can lead to cell membrane disruption in D. radiodurans [37]. We hypothesized that the loss of dsr11 may lead to changes in cell membrane function, thus affecting heat stress tolerance.…”
Section: Rna-seq Analysis Sheds New Light On the Mechanisms Of Dsr11-mentioning
confidence: 94%